2022
DOI: 10.3389/fonc.2022.762820
|View full text |Cite
|
Sign up to set email alerts
|

Disulfiram Transcends ALDH Inhibitory Activity When Targeting Ovarian Cancer Tumor-Initiating Cells

Abstract: Epithelial ovarian cancer (EOC) is a global health burden and remains the fifth leading cause of cancer related death in women worldwide with the poorest five-year survival rate of the gynecological malignancies. EOC recurrence is considered to be driven by the survival of chemoresistant, stem-like tumor-initiating cells (TICs). We previously showed that disulfiram, an ALDH inhibitor, effectively targeted TICs compared to adherent EOC cells in terms of viability, spheroid formation, oxidative stress and also p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
19
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 13 publications
(19 citation statements)
references
References 35 publications
0
19
0
Order By: Relevance
“…Numerous genes associated with stemness have been reported to be characteristic of OCSCs [ 30 , 31 ]. It was observed that 974 significantly decreased the expression of the well-known stemness genes Bmi-1, Nanog, Oct4, and Sox2 in OVCAR3 ( Figure 2 C) and OVCAR5 cells ( Figure 2 D).…”
Section: Resultsmentioning
confidence: 99%
“…Numerous genes associated with stemness have been reported to be characteristic of OCSCs [ 30 , 31 ]. It was observed that 974 significantly decreased the expression of the well-known stemness genes Bmi-1, Nanog, Oct4, and Sox2 in OVCAR3 ( Figure 2 C) and OVCAR5 cells ( Figure 2 D).…”
Section: Resultsmentioning
confidence: 99%
“…During the peritoneal dissemination, addition of genetic mutations and chromosomal aberrations are minimal, whereas the epigenetic dynamics facilitates the phenotypic plasticity of HGSC for adaptation to various microenvironments. Clinical trials for new drugs targeting the peritoneal dissemination of ovarian cancer are in preparation or ongoing [ 16 88 89 90 91 92 93 ] ( Table 1 ). Further studies on the dynamic biology of HGSC cells are needed to develop the epoch-making methods for prevention, early detection, and treatment for HGSC.…”
Section: Discussionmentioning
confidence: 99%
“…Cells were washed in PBS and resuspended in 400µl PBS for analysis on a BD FACSVerse cell analyzer (BD Biosciences, Franklin Lakes, NJ). Cell death was assessed by Annexin V (640905, Biolegend, San Diego, CA) and propidium iodide (PI) (R37169, Thermo Scientific, Waltham, MA) staining on cells treated as indicated, as previously described (30,50).…”
Section: Cytokine Arraymentioning
confidence: 99%
“…Cell lines and culture conditions Ovarian cancer lines were obtained as gifts, or from ATCC or NCI-60 as described and were cultured as described (53). TIC-enriching spheroid culture conditions are previously described (30,47,50). Briefly, spheroids were generated by maintaining cells in ultra-low attachment (ULA) plates or flasks (Corning, Corning, NY) in defined medium.…”
Section: Immunohistochemistry and Quantificationmentioning
confidence: 99%
See 1 more Smart Citation